The distance between two points with coordinates (x1, y1, z1) and (x2, y2, z2) is equal to `D = sqrt((x1 - x2)^2 + (y1 - y2)^2 + (z1 - z2)^2)`

To determine the distance between the points (-2, 3, -5) and (2, -4, 5) substitute the coordinates in the formula. The distance between the points is:

D = `sqrt((2 + 2)^2 + (3 + 4)^2 + (5 + 5)^2)`

= `sqrt(16 + 49 + 100)`

=` sqrt 165`

**The distance between (-2, 3, -5) and (2, -4, 5) is `sqrt 165` **

here two points given is in 3D cartesian plane.

Now the distance between two pont with the co-ordinates(x1,y2,z3) and (x2,y2,z3) is given by the formula

distance = √ {(x1-x2)^2 +(y1-y2)^2+(z1-z2)^2}

so the distance between the points (-2, 3, -5) and (2, -4, 5) would be

distance = √ {(-2-2)^2+(3+4)^2+(-5-5)^2}

=√{(-4)^2+(7)^2+(-10)^2} =√(16+49+100)=√165=12.85